1977
DOI: 10.1172/jci108649
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an important role of glucagon in the regulation of hepatic glucose production in normal man.

Abstract: A B S T R A C T To investigate the role of glucagon in regulating hepatic glucose production in man, selective glucagon deficiency was produced in four normal men by infusing somatostatin (0.9 mg/h) and regular pork insulin (150-,uU/kg per min) for 2 h. Exogenous glucose was infused to maintain euglycemia. Arterial plasma glucagon levels fell by greater than 50%o whereas plasma insulin levels were maintained in the range of 10-14 .uU/ml. In response to these hormonal changes, net splanchnic glucose production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(66 citation statements)
references
References 22 publications
5
61
0
Order By: Relevance
“…Not only is the liver very sensitive to changes in plasma glucagon, it also responds rapidly, with a half-maximal activation time of only 8 minutes (27). Human studies, although less well controlled, confirmed that the observations made in the dog extend to man (22)(23)(24)(25)(28)(29)(30). Thus, it is evident that after an overnight fast, basal levels of glucagon drive resting glucose production, thereby allowing insulin to link hepatic glucose output to the body's need for glucose.…”
Section: Metabolic Credentialsmentioning
confidence: 95%
See 1 more Smart Citation
“…Not only is the liver very sensitive to changes in plasma glucagon, it also responds rapidly, with a half-maximal activation time of only 8 minutes (27). Human studies, although less well controlled, confirmed that the observations made in the dog extend to man (22)(23)(24)(25)(28)(29)(30). Thus, it is evident that after an overnight fast, basal levels of glucagon drive resting glucose production, thereby allowing insulin to link hepatic glucose output to the body's need for glucose.…”
Section: Metabolic Credentialsmentioning
confidence: 95%
“…It is worth noting that glucose tolerance is not altered in muscle-specific insulin receptor KO mice (83) or in whole-body Glut4-null mice (84). In the normal dog and human, on the other hand, when insulin and glucagon secretion were simultaneously made deficient using somatostatin (30,85), insulin lack resulted in a significant decrease in glucose clearance and a consequent doubling of the plasma glucose level. Thus, in large mammals, the effect of insulin deficiency on muscle glucose uptake - at least acutely - is apparent even in the face of glucagon lack.…”
Section: Glucagonocentrism: Insulin Actions Are Mediated By Glucagonsmentioning
confidence: 99%
“…Glucagon is the primary controller of hepatic glucose production in the sedentary state (Liljenquist et al, 1977). Exercise is a robust challenge of the processes involved because of the high rates of glucose production necessary to maintain blood glucose (Wasserman, 2009).…”
Section: Control Of Muscle Glucose Influx During Exercisementioning
confidence: 99%
“…First, the glycemic response to suppression of both endogenous insulin and glucagon (among other effects) with somatostatin is biphasic, with an initial transient decrease in glucose production (3)(4)(5) and the plasma glucose concentration (4 -6), followed by an increase in glucose production (3)(4)(5) and the plasma glucose concentration (4 -6) in healthy humans. While these findings suggest an initial tonic effect of basal glucagon secretion to support the postabsorptive plasma glucose concentration, they suggest that suppression of insulin secretion is the dominant glycemic effect of somatostatin and, therefore, that insulin is the primary determinant of the postabsorptive plasma glucose concentration.…”
Section: Conclusion-thesementioning
confidence: 99%